Potential impact of genome editing in world agriculture - Jorge Martínez-Fortún; Dylan Phillips; Huw Jones (2017)
Changeable biotic and abiotic stress factors that affect crop growth and productivity, alongside a drive to reduce the unintended consequences of plant protection products, will demand highly adaptive farm management practices as well as access to continually improved seed varieties. The former is limited mainly by cost and, in theory, could be implemented in relatively short time frames. The latter is fundamentally a longer-term activity where genome editing can play a major role. The first targets for genome editing will inevitably be loss-of-function alleles, because these are straightforward to generate. In addition, they are likely to focus on traits under simple genetic control and where the results of modification are already well understood from null alleles in existing gene pools or other knockout or silencing approaches such as induced mutations or RNA interference. In the longer term, genome editing will underpin more fundamental changes in agricultural performance and food quality, and ultimately will merge with the tools and philosophies of synthetic biology to underpin and enable new cellular systems, processes and organisms completely. The genetic changes required for simple allele edits or knockout phenotypes are synonymous with those found naturally in conventional breeding material and should be regulated as such. The more radical possibilities in the longer term will need societal engagement along with appropriate safety and ethical oversight.